Protecting biodiversity via conservation networks: Taxonomic, functional, and phylogenetic considerations. (February 2023) - Willig, Michael R.; Presley, Steven J.; Klingbeil, Brian T.; Kosman, Evsey; Zhang, Tao; Scheiner, Samuel M.
Abstract: A key element of conservation action involves the incorporation of sites into networks of protected areas. Historically, most network-creation strategies have been based on considerations of species richness and site complementarity. Nonetheless, phylogenetic or functional biodiversity may be more critical to the maintenance of ecosystem resilience or functioning than is the number of species. Therefore, we explore the efficacy of three strategies (i.e., random, sequential, and simultaneous inclusion of sites into conservation networks of particular sizes) to maximize species richness in a network, and explore associated consequences to aspects of functional and phylogenetic biodiversity. We do so for passerines in Connecticut, bats in Paraguay, and trees in North Carolina, which differ in β, functional, and phylogenetic biodiversity. The efficacy of sequential and simultaneous strategies for conserving species richness are similar at all network sizes and represent improvements over random strategies for each of the three taxa, conserving all species in as few as 35 % of the sites required based on a random strategy. For aspects of functional and phylogenetic biodiversity, metrics converged on the value of the entire biota, even when networks contained as few as five sites, suggesting that richness-based approaches can be effective in guiding conservation action from multiple perspectives. Evaluation of networks intended to conserve biodiversity at spatial extents that include more complex environmental gradients than the examples presented here, or that comprise more heterogenous environments than those represented in our analyses, are needed to more fully explore the generality of our conclusions.